Getting the Opie We Deserve - Simmons, William J. (Göttingen, 2026)
This essay jumps off from two canonical texts in its reading of recent work by the queer-feminist contemporary photographer Catherine Opie: “Wide Open Spaces” by the American country bandThe Chicks and “Getting the Warhol We Deserve: Cultural Studies and Queer Culture” by Douglas Crimp. Part experimental nonfiction, part art history, part queer theory, “Getting the Opie We Deserve” invites projection and over-reading. It is as much about Opie’s work as it is about the queer project of hysterical investment and juxtaposition. Following the example of Eve Kosofsky Sedgwick, Lauren Berlant, José Esteban Muñoz, Maggie Nelson, and Anne Carson, the present work is another pole in the ongoing project of decentering established modes of critique.
Keywords: Kunst; Catherine Opie; Contemporary Art; Queer Formalism; Andy Warhol; Charlotte Brontë